2008
DOI: 10.1517/17425240802567846
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric carriers: role of geometry in drug delivery

Abstract: The unique properties of synthetic nanostructures promise a diverse set of applications as carriers for drug delivery, which are advantageous in terms of biocompatibility, pharmacokinetics, targeting and controlled drug release. Historically, more traditional drug delivery systems have focused on spherical carriers. However, there is a growing interest in pursuing non-spherical carriers, such as elongated or filamentous morphologies, now available due to novel formulation strategies. Unique physiochemical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 100 publications
1
136
0
1
Order By: Relevance
“…The motivation to develop particles with switchable shapes comes from the fact that shape has recently emerged as a crucial design parameter of micro-and nanoparticles (3,4,33,38,39). Studies have demonstrated that departure from the conventional spherical shape of particles brings unique and improved functionalities to the particulate systems, resulting in improved biological responses.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation to develop particles with switchable shapes comes from the fact that shape has recently emerged as a crucial design parameter of micro-and nanoparticles (3,4,33,38,39). Studies have demonstrated that departure from the conventional spherical shape of particles brings unique and improved functionalities to the particulate systems, resulting in improved biological responses.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of carrier deformability on their functionality in flow points to the idea of shape-adaptive carriers that are able to dynamically configure their overall morphology to respond to their local vascular environment in a manner similar to RBCs. As mentioned previously, a PEG coating is commonly used for enhancing circulation half-life and minimizes RES clearance by masking the carrier with a hydration stealth layer (47).…”
Section: Next-generation Vcs: ''Shape-adaptive'' Designmentioning
confidence: 99%
“…Such amphiphilic polymers form in water solution micelle-like structures (MLS) [28] or vesicles [35]. The architecture and functionality of grafted side branches, as well as the grafting degree cause a direct influence on the parameters and morphology of selforganized colloidal structures formed by the molecules of functional comb-like polymeric surfactants in solution [17,28,32,36,37].…”
Section: Introductionmentioning
confidence: 99%